Ethical challenges in qualitative sociology: a systematic literature review - Scheytt, Carla; Pflüger, Jessica (Frontiers in Sociology, 2024)
Qualitative researchers often encounter ethical challenges during their research process. Due to the large number of papers in which researchers reflect on specific and various ethical challenges within their projects, it proves difficult to keep track of them. To capture these reflexive practices, we conducted a literature review of 72 papers in sociology. Our review shows who reflects on research ethics and when and where such reflections occur. We identify 11 ethical issues that sociologists reflect on. Some issues address the challenges of implementing established ethical principles, such as (1) informed consent, (2) voluntary participation, (3) avoiding harm, (4) anonymization, and (5) confidentiality. Others go beyond these principles and refer to (6) the relationship between researchers and participants, (7) power asymmetries, (8) protecting yourself as a researcher, (9) deviant actions, (10) covert research, and (11) leaving the field. Our findings help researchers gain an overview of ethical challenges, enhancing their reflexivity.